2011
DOI: 10.2337/db10-0796
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Enhances Glucose-Stimulated Insulin Secretion From Pancreatic β-Cells

Abstract: OBJECTIVE Interleukin-6 (IL-6) has a significant impact on glucose metabolism. However, the effects of IL-6 on insulin secretion from pancreatic β-cells are controversial. Therefore, we analyzed IL-6 effects on pancreatic β-cell functions both in vivo and in vitro. RESEARCH DESIGN AND METHODS First, to examine the effects of IL-6 on in vivo insulin secretion, we expressed IL-6 in the livers of mice using the adenoviral gene transfer system. In addition, using both MIN-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 49 publications
4
88
0
1
Order By: Relevance
“…The activation of PLC has been implicated in the mechanism of calcium release and activation of other secondary effectors that mediate insulin secretion [26]. In addition, it has been demonstrated that IL-6 activates the PLC pathway in different cell types [22], including beta cells [25]. Concordant with these results, Suzuki et al [25] showed that different PLC inhibitors were able to block insulin secretion mediated by IL-6.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The activation of PLC has been implicated in the mechanism of calcium release and activation of other secondary effectors that mediate insulin secretion [26]. In addition, it has been demonstrated that IL-6 activates the PLC pathway in different cell types [22], including beta cells [25]. Concordant with these results, Suzuki et al [25] showed that different PLC inhibitors were able to block insulin secretion mediated by IL-6.…”
Section: Resultssupporting
confidence: 71%
“…In addition, it has been demonstrated that IL-6 activates the PLC pathway in different cell types [22], including beta cells [25]. Concordant with these results, Suzuki et al [25] showed that different PLC inhibitors were able to block insulin secretion mediated by IL-6. Therefore, we tested the effect of treating MIN6B1 cells with the PLC inhibitor neomycin (10 μmol/l) (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…2). Higher concentrations of IL6 (600-1200 pg/ml) were recently reported to significantly increase insulin secretion from mouse islets and also MIN6 b-cells (Suzuki et al 2011), but the physiological significance of such a high-concentration finding remains to be established. The authors speculate that IL6 b-cell action is of physiological importance following termination of exercise in vivo, when insulin secretion and subsequent action at the level of skeletal muscle will aid in recovery mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The list of adipokines known to regulate glucose homeostasis increases every year, with reports identifying MCP-1 [73], IL-6 [74], IL-1β (Interleukin-1 beta) [75], adipolin [76], omentin [77] and even DPP4 (Dipeptidyle Peptidase 4) [78] have been identified as fat-secreted molecules that can regulate either insulin secretion or action. This list will no doubt continue to increase and the prospect of adipokines providing a defining link between obesity and type 2 diabetes remains a tantalizing possibility.…”
Section: Other Adipokinesmentioning
confidence: 99%